Engineering workshop practices : mechanical stream. - Gain, John. (South Melbourne : Thomas Nelson Australia, 1996)
This book is about: Working safety; Measurement; Measuring tools; Gauges; Cutting tool materials; ...
Keywords: Machine-tools.; Machine-tools.